2019
DOI: 10.1038/s41467-019-08576-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing identifies ADGRG6 enhancer mutations and FRS2 duplications as angiogenesis-related drivers in bladder cancer

Abstract: Bladder cancer is one of the most common and highly vascularized cancers. To better understand its genomic structure and underlying etiology, we conduct whole-genome and targeted sequencing in urothelial bladder carcinomas (UBCs, the most common type of bladder cancer). Recurrent mutations in noncoding regions affecting gene regulatory elements and structural variations (SVs) leading to gene disruptions are prevalent. Notably, we find recurrent ADGRG6 enhancer mutations and FRS2 duplications which are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 51 publications
4
66
0
1
Order By: Relevance
“…The most frequently mutated gene, GPR126, is a G-protein coupled receptor that can bind to basement membrane protein type IV collagen [29]. The effects of the non-coding mutations in GPR126 have recently been investigated in 2 studies with apparently discordant results [21,22]. In a series of 196 patients, Wu et al reported that GPR126 mutations are more common in older patients and in NMIBC rel- ative to MIBC, and immunohistochemistry showed that UBCs with mutations expressed more GPR126 protein [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most frequently mutated gene, GPR126, is a G-protein coupled receptor that can bind to basement membrane protein type IV collagen [29]. The effects of the non-coding mutations in GPR126 have recently been investigated in 2 studies with apparently discordant results [21,22]. In a series of 196 patients, Wu et al reported that GPR126 mutations are more common in older patients and in NMIBC rel- ative to MIBC, and immunohistochemistry showed that UBCs with mutations expressed more GPR126 protein [21].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the non-coding mutations in GPR126 have recently been investigated in 2 studies with apparently discordant results [21,22]. In a series of 196 patients, Wu et al reported that GPR126 mutations are more common in older patients and in NMIBC rel- ative to MIBC, and immunohistochemistry showed that UBCs with mutations expressed more GPR126 protein [21]. They also demonstrated significantly worse overall survival for both NMIBC and MIBC patients with mutations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dey's team launched a research that inhibition of FRS2 could block the PI3K/AKT signaling to induce apoptosis and suppress the proliferation and translocation in breast cancer . Song Wu et al figured out that FRS2 had an obviously upregulation in bladder cancer through whole‐genome sequencing, which could recruit endothelial cells and induce tube formation . Based on these studies, we conducted immunohistochemistry in GCTB tissues and adjacent normal tissues, and found that FRS2 was highly expressed in tumor tissues.…”
Section: Discussionmentioning
confidence: 91%